(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
As a significant component of school culture, the dormitory plays vital parts in ideological and extra-class education. Dormitory culture, with its practical cultivation, has gained increasingly wide attention nowadays. Through studies about the meaning, features and functions of dormitory, this work further elaborated its specific cultivation value.